Modification Curriculum in Inclusive Setting: A Systematic Literature Review - Nurjannah, Siti; Azizah, Nur; Rosi, Fahrur (JPK (Jurnal Pendidikan Khusus), 2023)
This article aims to explore the implementation of modification curriculum adapted in schools in Yogyakarta. The curriculum plays a crucial role in education and serves as a fundamental guide for effective instructional practices. Ensuring the proper implementation of the curriculum in inclusive education is crucial to ensure that children with special needs receive an educational curriculum that aligns with their abilities. This study aims to systematically review articles discussing the implementation of curriculum for students with special needs in inclusive schools within the Province of D.I Yogyakarta, Indonesia. The researchers employed a systematic literature review (SLR) method by analyzing 13 relevant articles. The writing process followed the guidelines outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The findings indicated that not all-inclusive schools in Yogyakarta have implemented curriculum modifications for students with special needs. However, several research mentioned that certain schools have undertaken curriculum modification processes. The discussion section highlighted various obstacles hindering the implementation of curriculum modifications in schools providing inclusive education.